2011
DOI: 10.1080/14766086.2011.630169
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, religion, and emotional labor in the workplace

Abstract: Emotional labor is the regulation of emotional displays as part of a work role. To date, minimal research has considered how spirituality and religion impact the performance and consequences of emotional labor, which is an important omission given a growing awareness that religion and spirituality are important components of people’s lives that continue to inform their feelings, thoughts, and behaviors while at work. Accordingly, we review the literature on emotional labor and develop a series of research que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 64 publications
0
39
0
1
Order By: Relevance
“…The concept of emotional labour was first introduced by Hochschild (1983) based on her studies of flight attendants, but ensuing research has found emotional labour to be usual in a number of human service occupations and a sizeable predictor of strain in the workplace (Brotheridge, 2006 (Byrne, Morton, & Dahling, 2011). These rules typically forms part of an organization's policy, clarifying which emotions the organization considers apt to show to clients (van Gelderen et al, 2011) or implicit and internalized via experience and socialization into a profession and/or a particular organization (Byrne et al, 2011).…”
Section: Emotional Labour and Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of emotional labour was first introduced by Hochschild (1983) based on her studies of flight attendants, but ensuing research has found emotional labour to be usual in a number of human service occupations and a sizeable predictor of strain in the workplace (Brotheridge, 2006 (Byrne, Morton, & Dahling, 2011). These rules typically forms part of an organization's policy, clarifying which emotions the organization considers apt to show to clients (van Gelderen et al, 2011) or implicit and internalized via experience and socialization into a profession and/or a particular organization (Byrne et al, 2011).…”
Section: Emotional Labour and Burnoutmentioning
confidence: 99%
“…These rules typically forms part of an organization's policy, clarifying which emotions the organization considers apt to show to clients (van Gelderen et al, 2011) or implicit and internalized via experience and socialization into a profession and/or a particular organization (Byrne et al, 2011).…”
Section: Emotional Labour and Burnoutmentioning
confidence: 99%
“…There is a growing body of research on emotions in the workplace (Ashkanasy et al, 2002;Byrne et al, 2011;Mukhopadhyay, 2012;Rumens, 2005), described as "an explosion of interest in emotion in organizational behavior" (Fineman, 2004, p. 720). Usually there is a predominant emphasis on emotion display rules in organizations; however recent studies have highlighted the need for a more nuanced understanding of emotional labor (O'Donohoe and Turley, 2006).…”
Section: Contextual Emotional Labormentioning
confidence: 99%
“…Byrne et al (2011) note that to date, minimal research has considered how spirituality and religion impact the performance and consequences of emotional labor, which is an important omission given that religion and spirituality are important components of people's lives that continue to inform GM 28,4 their feelings, thoughts, and behaviors while at work. The contextual approach recognizes the emotional labor implications of an employee's contact not only with the public but also with her colleagues and other members of the society and the workplace.…”
Section: Contextual Emotional Labormentioning
confidence: 99%
See 1 more Smart Citation